Development of a method for quantitative determination of the cytotoxic agent piplartine (piperlongumine) in multiple skin layers. (23rd October 2018) - Carvalho, Vanessa F. M.; Giacone, Daniela V.; Costa‐Lotufo, Leticia V.; Silveira, Edilberto Rocha; Lopes, Luciana B.
Abstract: This study reports the development of a simple and reproducible method, with high rates of recovery, to extract the cytotoxic agent piplartine from skin layers, and a sensitive and rapid UV‐HPLC method for its quantification. Considering the potential of piplartine for topical treatment of skin cancer, this method may find application for formulation development and pharmacokinetics studies to assess cutaneous bioavailability. Porcine skin was employed as a model for human tissue. Piplartine was extracted from the stratum corneum (SC) and remaining viable skin layers (VS) using methanol, vortex homogenization and bath sonication, and subsequently assayed by HPLC using a C18 column, and 1:1 (v/v) acetonitrile–water (adjusted to pH 4.0 with acetic acid 0.1%) as mobile phase. The quantification limit of piplartine was 0.2 μg/mL (0.6 μm ), and the assay was linear up to 5 μg/mL (15.8 μm ), with within‐day and between‐days assay coefficients of variation and relative errors <15%. Piplartine recovery from SC and VS varied from 86 to 96%. The method was suitable to assay samples from skin penetration studies, enabling detection of differences in cutaneous delivery in different skin compartments resulting from treatment with various formulations and time periods.